Coal Spontaneous Combustion Theory with Chain Self-promoted Oxidizing Induced by Active Group - Deng, Jun; Li, Yaqing; Heris, Saeid Zeinali; Shu, Chi-Min (Springer Nature Singapore : Imprint: Springer, 2025)
XXII, 199 p. 219 illus., 158 illus. in color.